The Role of Social Media in Islamic Religious Education: Challenges and Opportunities in the Digital Era - Rizky Giansyah Putra; Nadia Yusri; Silvia Fauziah Sinaga (Jurnal Pendidikan Islam, 2024)
his research plays a crucial role in highlighting the significance of Islamic religious education in the digital era, presenting both challenges and opportunities. Social media serves as an effective platform for disseminating religious information, facilitating religious discussions, and broadening the reach of religious education across various segments of society, particularly among the youth. However, the use of social media in this context also brings forth challenges such as unverified information, inappropriate content, and the potential exposure to views that are inconsistent with religious teachings. This study aims to delve deeply into the role of social media in Islamic religious education, identifying key challenges faced and discussing various opportunities that can be leveraged. Qualitative research methods were employed to gather data through in-depth interviews with active social media users engaged in Islamic religious education contexts. The findings indicate that while social media offers broad and rapid access to religious information, users need to exercise wisdom in managing and evaluating the accuracy of the information they receive.